Are rapidly growing cancers more lethal?. (February 2017) - Adami, Hans-Olov; Csermely, Peter; Veres, Daniel V.; Emilsson, Louise; Løberg, Magnus; Bretthauer, Michael; Kalager, Mette
Abstract: The view, that rapidly growing tumours are more likely than slow-growing tumours to metastasize and become lethal, has remained almost axiomatic for decades. Unaware of any solid evidence supporting this view, we undertook an exhaustive system-level analysis of intra- and intercellular signalling networks. This analysis indicated that rapid growth and metastasis are often different outcomes of complex integrated molecular events. Evidence from humans can be derived chiefly from screening interventions because interval cancers that surface clinically shortly after a negative screening test are, on average, more rapidly growing than cancers not detected by screening. We reviewed all available data limited to cancers of the breast, cervix and large bowel. The evidence from humans provides no support for the theory that rapidly growing cancers are more prone to metastasize. These findings indicate that the prevailing view should be reconsidered, as should the impact of length-biased sampling in cancer screening, and the findings provide no support for treating interval cancers more aggressively than non-interval cancers. Highlights: The view that rapidly growing tumors are more lethal has remained almost axiomatic for decades. Rapid growth and metastases formation are often different outcomes of complex integrated molecular events. In humans interval cancers are more rapidly growing than cancers unaffected by screening. Cancers of the breast, cervix and large bowel, do not support the theory that rapidly growing cancers are more lethal. Existing evidence provide no support for treating interval cancers more aggressively than non-interval cancers.